Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/tbj.12352
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Prevention

Abstract: Breast cancer is the most common cancer in women with 232,670 new cases estimated in the USA for 2014. Approaches for reducing breast cancer risk include lifestyle modification, chemoprevention, and prophylactic surgery. Lifestyle modification has a variety of health benefits with few associated risks and is appropriate for all women regardless of breast cancer risk. Chemoprevention options have expanded rapidly, but most are directed at estrogen receptor positive breast cancer and uptake is low. Prophylactic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…In addition, advances in molecular science and recognition of prognostic and predictive factors led to the novel, effective and individualized therapy . More importantly, the discovery of breast cancer susceptibility genes and the intensive efforts to identify risk factors served as a promise for early detection of breast cancer precursors and breast cancer prevention . Associated with the above‐mentioned changes, the availability of risk‐reduction modalities has proven validity in offering better quality of life for high‐risk patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, advances in molecular science and recognition of prognostic and predictive factors led to the novel, effective and individualized therapy . More importantly, the discovery of breast cancer susceptibility genes and the intensive efforts to identify risk factors served as a promise for early detection of breast cancer precursors and breast cancer prevention . Associated with the above‐mentioned changes, the availability of risk‐reduction modalities has proven validity in offering better quality of life for high‐risk patients.…”
Section: Introductionmentioning
confidence: 99%
“…Currently breast cancer prevention mainly includes three strategies: lifestyle modification, chemoprevention, and prophylactic surgery. Although alcohol consumption, obesity, and hormone replacement therapy have been evaluated as independent risk factors for breast cancer, there is no specific guideline for dietary or physical activity intervention specifically to prevent breast cancer 5 . Because of the lack of strong evidence and high-quality clinical trials, lifestyle adjustments are only recommended to patients as a supplemental measure in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to prophylactic surgery, bilateral salpingoophorectomy and mastectomy are recommended to high-risk patients, especially those who carry the BRCA1/2 mutation 12 . Numerous retrospective and cohort studies have suggested that prophylactic mastectomy could reduce the risk of breast cancer by more than 90% 5 . However, mastectomy does not completely eliminate the risk of breast cancer because it is impossible to eradicate all terminal duct-lobular units in many women.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to primary prevention (ie, all the interventions capable of reducing the occurrence of new cases), several approaches have been proposed and tested, such as lifestyle changes (including smoking cessation and active exercise), prophylactic surgery, and chemoprevention (also known as preventive therapy [8]) (9)(10)(11). Although lifestyle changes are broadly recommended for their undoubted effectiveness on a range of malignant and nonmalignant illnesses, the magnitude of their review impact specifically on breast cancer incidence has been questioned (12).…”
mentioning
confidence: 99%
“…Internationally trusted guidelines (eg American Society of Clinical Oncology [ASCO] [21], National Comprehensive Cancer Network [NCCN] [22], US Preventive Services Task Force [23], National Institute for Health and Care Excellence [NICE] [24]) do recommend the use of some hormone-related CPAs in high-risk women, although the uptake is low mainly because of the associated adverse effects (10,11,25). Randomized controlled trials (RCTs) and meta-analyses of single CPAs support these guidelines (26).…”
mentioning
confidence: 99%